Foreign investment, human rights, and environmental protection striking a balance for sustainable development - Alam, Shawkat; Faruque, Abdullah al (Abingdon, Oxon Routledge, 2025)
This book examines the integration of human rights and environmental standards within international investment agreements (IIAs). It explores the intricate relationship between foreign direct investment (FDI) and sustainable development, emphasizing the necessity for reform in investment treaties to ensure they support rather than hinder human rights and environmental protection. The book begins with an overview of the current international investment law landscape, focusing on its primary goal of investment protection. It then delves into how human rights and environmental standards can shape IIAs, suggesting a new approach to these treaties. The authors explore the incorporation of sustainable development principles into IIAs, the difficulty of balancing investor protection with state regulatory autonomy, and the evolving norms and standards in this area. The book includes detailed case studies on topics such as the interplay between labour standards, investment, and human rights, bilateral investment agreements, sustainable forest management, and the liberalization of water services. Aimed at policymakers, legal scholars, and international law practitioners, this book provides a thorough framework for understanding and reforming IIAs. It offers groundbreaking insights into aligning investment treaties with global sustainable development goals, making it a vital resource for anyone interested in the intersection of investment, human rights, and environmental sustainability"--
Bridging investment and sustainability : the role of human rights and environmental standards in shaping international investment agreements--Reimagining investment treaties : converging human rights and environmental protection through relevant actors--Conceptual framework for integrating human rights and sustainable development into international investment agreements--Investment protection, human rights, and environmental sustainability : emerging standards and evolving norms--Human rights and environmental protection : addressing substantive challenges in regional and bilateral investment agreements--Investor-state dispute settlement : harmonizing investment protection with human rights and sustainability--Business and human rights : the interplay between labour standards, investment and human rights--Promoting sustainable forest management through international trade and investment--GATS and the liberalization of water services : implications for human rights and the environment.
Includes bibliographical references and index.
Keywords: Investments, Foreign (International law); Investments, Foreign -- Law and legislation; Environmental law, International; International commercial arbitration; International law and human rights; Social responsibility of business -- Law and legislation; Sustainable development -- Law and legislation